1900 Ohio Gen. and Local Acts 235, An Act to Amend Section 6961 of the Revised Statutes (Bates' Annotated) of Ohio, § 1 (vol. 94) - (:unkn) unknown (General Publisher, 1900)
No person shall, at any time, catch, kill, or injure, or pursue, with such intent any wild duck or wild goose, by the aid or use of any swivel or punt gun, or any other gun but a common shoulder gun.
--
Keywords: HUNTING REGULATION